(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the effects of the supreme secondary learners’ government policies and its goal for student welfare in Cluster 5, Davao City Schools Division. The study used a non-experimental descriptive-correlational research design, utilizing an adapted survey instrument to gather responses from the 120 randomly selected teacher-respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r and Simple Linear Regression Analysis. Findings revealed that supreme secondary learners’ government policies is sometimes manifested, thus, moderately extensive, and, likewise, learner’s Safety is sometimes manifested, thus, moderately extensive. There is a significant correlation between the supreme secondary learner government (SSL) structure and school policies affecting learner safety. All domains of supreme secondary learner government policies in terms of representation and diversity, budget resource allocation, advocacy and policy influence, collaboration with school administration, and training and development significantly influence learner safety. Future research may provide insights into the sustainability of the influence of SSLGs on safety policies over time.